AGO Recommendations for the Diagnosis and Treatment of Patients with Locally Advanced and Metastatic Breast Cancer: Update 2022. - Thill, Marc; Lueftner, Diana; Kolberg-Liedtke, Cornelia; Albert, Ute-Susann; Banys-Paluchowski, Maggie; Bauerfeind, Ingo; Blohmer, Jens-Uwe; Budach, Wilfried; Dall, Peter; Fallenberg, Eva Maria; Fasching, Peter; Fehm, Tanja; et al. (Breast Care, 2022)
The Breast Committee of the Arbeitsgemeinschaft Gynäkologische Onkologie (German Gynecological Oncology Group, AGO) presents the 2022 update of the evidence-based recommendations for the diagnosis and treatment of patients with locally advanced and metastatic breast cancer.
EVALuna2:514465